A miniaturized high‐performance broadband absorber based on 2.5‐D meander lines and magnetic materials at low frequencies. Issue 5 (18th February 2021) - Zhang, Xuewei; Liu, Shaobin; Yu, Qiming; Wang, Lingling; Liao, Kun
Abstract: A miniaturized metamaterial absorber (MA) with resistive 2.5‐dimensional (2.5‐D) meander lines (ML) and magnetic materials (MM) layer backed by a conducting ground, which exhibits good absorbing performance, is designed and experimentally demonstrated. The 2.5‐D layer is two pairs of ML are connected in series by the four vias cross dipole structure where resistive sheets are loaded on both sides. The MM substrate has both high permeability and permittivity for bandwidth expanding at low frequencies. The 2.5‐D layer and MM layer are separated by an air layer. In the positive resonance region of air layer, strong magnetic squeezing effect occurs. This results in significant magnetic field enhancement within the MM layer. Results indicate that an absorption at lower frequencies is significantly enhanced and is above 90% in 0.8 to 3.2 GHz at normal incidence and the relative bandwidth is 120%. A key feature of the proposed absorber is that its unit cell is only 0.019 λ L  × 0.019 λ L, which exhibits satisfactory stability for different polarization states and incident angles. Experimental results are presented and compared to numerical simulations, showing a reasonable agreement. This work providing new ways for miniaturized high‐performance absorbing materials of wider bandwidth and stronger absorption.